2017
DOI: 10.1093/mnras/stx3112
|View full text |Cite
|
Sign up to set email alerts
|

First results from the IllustrisTNG simulations: the stellar mass content of groups and clusters of galaxies

Abstract: The IllustrisTNG project is a new suite of cosmological magneto-hydrodynamical simulations of galaxy formation performed with the AREPO code and updated models for feedback physics. Here we introduce the first two simulations of the series, TNG100 and TNG300, and quantify the stellar mass content of about 4000 massive galaxy groups and clusters (10 13 M 200c /M 10 15 ) at recent times (z 1). The richest clusters have half of their total stellar mass bound to satellite galaxies, with the other half being associ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

93
1,422
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,559 publications
(1,517 citation statements)
references
References 118 publications
93
1,422
1
1
Order By: Relevance
“…Illus-trisTNG is the successor to the Illustris simulations (see below), with numerous updates that are described in the public data release (Nelson et al 2019). Weinberger et al (2018) and Pillepich et al (2018a) provide a complete description of the physical models. Additional details about these simulations are given by Pillepich et al (2018b), Springel et al (2018), Nelson et al (2018), Naiman et al (2018), and Marinacci et al (2018).…”
Section: The Illustristng Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Illus-trisTNG is the successor to the Illustris simulations (see below), with numerous updates that are described in the public data release (Nelson et al 2019). Weinberger et al (2018) and Pillepich et al (2018a) provide a complete description of the physical models. Additional details about these simulations are given by Pillepich et al (2018b), Springel et al (2018), Nelson et al (2018), Naiman et al (2018), and Marinacci et al (2018).…”
Section: The Illustristng Simulationsmentioning
confidence: 99%
“…The baryonic simulations follow the evolution of dark matter, stars, gas and supermassive black holes from a redshift of 127 to the present epoch using the AREPO moving-mesh code (Springel 2010). Star formation occurs above a threshold density criterion, and is regulated by a subgrid model for the interstellar medium (Springel & Hernquist 2003;Nelson et al 2015;Pillepich et al 2018a). Where needed for stellar evolution and mass return calculations, a Chabrier (2003) initial mass function is used.…”
Section: The Illustristng Simulationsmentioning
confidence: 99%
“…But this simple model ignores non-spherical and non-gravitational effects such as hierarchical mergers driven by large-scale filaments and feedback by star formation, supernovae, and active galactic nuclei (AGN). A central focus of recent observations and modern simulations has been on understanding these non-gravitational effects and feedback processes, which leads to a comprehensive understanding of the ways in which the galaxies are forming and evolving as a function of their host halo mass and redshift (McCarthy et al 2017;Pillepich et al 2018b;Mulroy et al 2019). While the first principle approaches have been made progress in making more realistic galaxy population, empirical approaches are complementary in gaining insight into the physics of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations (e.g., Oser et al 2010;Wellons et al 2015), semi-analytic models (SAM; e.g., Lee & Yi 2013, 2017, and stellar-mass-halo-mass (SHAM) analyses (e.g., Moster et al 2013Moster et al , 2018Behroozi et al 2013b;Rodríguez-Puebla et al 2017) generally show that the fraction of accreted stars through mergers increase with total galaxy stellar mass or halo mass (e.g., Lackner et al 2012;Cooper et al 2013;Rodriguez-Gomez et al 2016;Qu et al 2017;Pillepich et al 2018). For example, Qu et al (2017) analyzed the mass assembly of central galaxies in the EA-GLE cosmological simulation and found that ∼ 20% of the stellar mass of present day massive galaxies (> 10 11 M ) is built up through mergers, and more massive galaxies have experienced more stellar-mass growth by mergers.…”
Section: Introductionmentioning
confidence: 99%